2002
DOI: 10.3317/jraas.2002.046
|View full text |Cite
|
Sign up to set email alerts
|

Review: The pharmacokinetics and pharmacodynamics of angiotensin-receptor blockers in end-stage renal disease

Abstract: Angiotensin-converting enzyme (ACE) inhibitors and more recently angiotensin-receptor blockers (ARBs) have become popular therapies in the end-stage renal disease (ESRD) patient. The ability of either of these drug classes to reduce blood pressure in the ESRD patient is well accepted; however, there is considerably less information available to guide the clinician in the safe and effective use of these drugs in the ESRD patient with congestive heart failure and/or coronary artery disease. Head-to-head studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 105 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…They may lower the risk for myocardial infarction 7 , improve the treatment of patients in end stage renal disease 75 , decrease the incidence of stroke 38, 61 , and improve stroke outcome 2 . Because of the antagonist relations between the ACE2/Ang-(1-7)/Mas axis and the Ang-II/AT1 pathway, others have suggested that augmentation of Mas signaling by pharmacological or genetic methods also may be a means of improving outcomes in these pathological situations 17, 52 .…”
Section: Discussionmentioning
confidence: 99%
“…They may lower the risk for myocardial infarction 7 , improve the treatment of patients in end stage renal disease 75 , decrease the incidence of stroke 38, 61 , and improve stroke outcome 2 . Because of the antagonist relations between the ACE2/Ang-(1-7)/Mas axis and the Ang-II/AT1 pathway, others have suggested that augmentation of Mas signaling by pharmacological or genetic methods also may be a means of improving outcomes in these pathological situations 17, 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, renal impairment differentially affects ARB pharmacokinetics, with irbesartan and telmisartan not being affected even by severe renal impairment. As ARBs pharmacodynamically have beneficial effects in patients with impaired renal function and are generally classified as renoprotective, their use in such patients is generally recommended (Sica and Gehr, 2002).…”
Section: F Renal and Hepatic Impairmentmentioning
confidence: 99%
“…To our knowledge, the impact of ACE-I and ARB use on inhibition of the positive hematologic effects of renin-angiotensin system activation has been studied thoroughly only in patient populations at risk for secondary erythrocytosis [5][6][7][8][9][10][11] but not in most patients taking these pharmaceuticals for indications such as diabetes, hypertension, IHD, and left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%